Necropolitical changes and repressive strategies on an Amazonian capitalistic frontier: Xambioá town, Tocantins, Brazil - De Abreu e Souza, Rafael (Brasiliana: Journal for Brazilian Studies, 2021)
This paper analyzes material changes undergone by the town of Xambioá, Tocantins State, Northern Brazil in a time of State terrorism. It argues that such changes were the product of the necropolitical approach materialized by a repressive system implemented and guided by the Brazilian Dictatorship along the lines of doctrines of national security. It focuses on the interaction between the town and the actions of repression undertaken against an Amazonian armed movement, the 1970s Araguaia Guerrilla, by which the Communist Party of Brazil aimed to bring down the military through a massive peasant uprising. For this urban archaeology of State terrorism, this work uses remote sensing, spatial syntax, and urban morphology, unveiling the material ruptures and terrorscapes that made up a new ontology established in the Bico do Papagaio region to instil fear, in order to control and silence residents.